Equilibrium states for hyperbolic potentials. (11th January 2017) - Ramos, Vanessa; Viana, Marcelo
Abstract: We prove the existence of finitely many ergodic equilibrium states for local homeomorphisms and hyperbolic potentials. We also deal with partially hyperbolic skew-products over non-uniformly expanding maps with uniform contraction on the fibre. For these systems we prove the existence and finiteness of the equilibrium states associated with a class of Hölder continuous potentials.